Physicians’ Perceptions of Clinical Utility of a Digital Health Tool for Electronic Patient-Reported Outcome Monitoring in Real-Life Hematology Practice. Evidence From the GIMEMA-ALLIANCE Platform - Efficace, Fabio; Patriarca, Andrea; Luppi, Mario; Potenza, Leonardo; Caocci, Giovanni; Tafuri, Agostino; Fazio, Francesca; Cartoni, Claudio; Petrucci, Maria Teresa; Carmosino, Ida; Moia, Riccardo; Margiotta Casaluci, Gloria; et al. (Frontiers in Oncology, 2022)
Digital health tools are increasingly being used in cancer care and may include electronic patient-reported outcome (ePRO) monitoring systems. We examined physicians’ perceptions of usability and clinical utility of a digital health tool (GIMEMA-ALLIANCE platform) for ePRO monitoring in the real-life practice of patients with hematologic malignancies. This tool allows for the collection and assessment of ePROs with real-time graphical presentation of results to medical staff. Based on a predefined algorithm, automated alerts are sent to medical staff. Participating hematologists completed an online survey on their experience with the platform. Of the 201 patients invited to participate between December 2020 and June 2021 (cut-off date for current analysis), 180 (90%) agreed to enter the platform and had a median age of 57 years. Twenty-three hematologists with a median age of 42 years and an average of 17 years of experience in clinical practice were surveyed. All hematologists agreed or strongly agreed that the platform was easy to use, and 87% agreed or strongly agreed that ePROs data were useful to enhance communication with their patients. The majority of physicians (78%) accessed the platform at least once per month to consult the symptom and health status profile of their patients. The frequency of access was independent of physician sex (p=0.393) and years of experience in clinical practice (p=0.404). In conclusion, our preliminary results support the clinical utility, from the perspectives of the treating hematologist, of integrating ePROs into the routine cancer care of patients with hematologic malignancies.